Extrusion of CuZn39Pb2 Alloy by the KOBO Method - Bochniak, W.; Korbel, A. (Engineering Transactions, 1999)
Design of intelligent technologies based on the structural criterion is intended both to reduce the work of plastic deformation and to generate advantageous structure and mechanical parameters of metallic products. It enables external control of the deformation mechanism oriented towards time-spatial organization of the slip and localization of plastic flow in the transgranular shear bands. One of the industrial solutions presented in the paper refers to the production of rods of lead brass by the KOBO method, consisting in a complex extrusion of the ingot on a press with reversibly rotating die. The performed experimental investigations and their analysis comprised the mechanical aspects of the new, energy-saving technology of metal working and were concentrated on the evaluation of the possibility of formation of the final structure and by that means, of the expected mechanical properties of the products.